Motor performance of children and adolescents with cerebral palsy during the execution of computer tasks with different peripherals - Spiller, Marcelo Grandini; Audi, Mauro; Braccialli, Lígia Maria Presumido (ABRAMO Associação Brasileira de Motricidade Orofacial, 2019)
ABSTRACTObjective: to assess the effectiveness of using different input devices for computer access by children and adolescents with cerebral palsy and to verify the relationship of performance with age and level of motor classification.Methods: the study included 14 children and adolescents with cerebral palsy, aged 6 to 14 years, with Gross Motor Function Classification System (GMFCS) and Manual Ability Classification System (MACS) levels from I to V. The participants’ performance was observed during the use of touch screen, conventional mouse and eye tracking mouse in performing specific tasks with softwares Discrete Aiming Task 2.0, Tracking Task 2.0 and Single Switch Performance Test (SSPT) 1.0. The following variables were analyzed: response time, frequency of errors, mean time to activate input devices, relationship between satisfaction with input devices and motor skill level.Results: results indicated significant differences in response time, frequency of errors, and triggering mean time depending on the input device used, and correlation between the motor ability level and satisfaction, using the device, and between the level of manual ability and satisfaction with the mouse.Conclusion: the eye tracking mouse and the touch screen were the most effective devices during the execution of tasks on the computer by study participants.

RESUMOObjetivo: avaliar a eficácia de uso de diferentes dispositivos de entrada para o acesso ao computador por crianças e adolescentes com paralisia cerebral e verificar a relação do desempenho com a idade e o nível de classificação motora.Métodos: participaram do estudo 14 crianças e adolescentes com paralisia cerebral, com idade entre 6 e 14 anos, com níveis na Gross Motor Function Classification System (GMFCS) e na Manual Ability Classification System (MACS) de I a V. Foi verificado o desempenho dos participantes durante o uso de tela sensível ao toque, mouse convencional e mouse ocular, para realizar tarefas específicas com os softwares: o Discrete Aiming Task 2.0, o Tracking Task 2.0 e o Single Switch Performance Test (SSPT) 1.0 Foram analisadas as variáveis: tempo de resposta; frequência de erros; tempo médio para acionamento dos dispositivos de entrada, relação entre satisfação com os dispositivos de entrada e o nível de habilidade motora.Resultados: indicaram diferenças significantes no tempo de resposta; na frequência de erros; e no tempo médio para acionamento dependendo do dispositivo de entrada usado, e haver correlação entre o nível de habilidade motora e a satisfação de uso do dispositivo e entre o nível de habilidade manual e a satisfação com o mouse.Conclusão: o mouse ocular e a tela sensível ao toque foram os dispositivos mais eficazes durante a execução das tarefas no computador pelos participantes do estudo.
Desempenho motor de crianças e adolescentes com paralisia cerebral durante a execução de tarefas no computador com diferentes periféricos
Keywords: Cerebral Palsy; Self-Help Devices; Special Education; Information Technology; Paralisia Cerebral; Equipamentos de Autoajuda; Educação Especial; Tecnologia da Informação